Susceptibility to Nisin, Bactofencin, Pediocin and Reuterin of Multidrug Resistant Staphylococcus aureus, Streptococcus dysgalactiae and Streptococcus uberis Causing Bovine Mastitis - Samantha Bennett (MDPI AG, 2021)
Antibiotics are the most effective strategy to prevent and treat intramammary infections. However, their misuse has led to the dissemination of multidrug resistant bacteria (MDR) for both animals and humans. Efforts to develop new alternative strategies to control bacterial infections related to MDR are continuously on the rise. The objective of this study was to evaluate the antimicrobial activity of different bacteriocins and reuterin against MDR Staphylococcus and Streptococcus clinical isolates involved in bovine mastitis. A bacterial collection including S. aureus (n = 19), S. dysgalactiae (n = 17) and S. uberis (n = 19) was assembled for this study. Antibiotic resistance profiles were determined by the disk diffusion method. In addition, sensitivity to bacteriocins and reuterin was evaluated by determining minimum inhibitory concentrations (MIC). A total of 21 strains (37.5%) were MDR. MICs ranged from ≤1.0 <semantics>μ</semantics>g/mL to ≥100 <semantics>μ</semantics>g/mL for nisin and 2.0 to ≥250 <semantics>μ</semantics>g/mL for bactofencin. Reuterin was active against all tested bacteria, and MICs vary between 70 and 560 <semantics>μ</semantics>g/mL. Interestingly, 20 MDR strains were inhibited by bactofencin at a concentration of ≤250 <semantics>μ</semantics>g/mL, while 14 were inhibited by nisin at an MIC of ≤100 <semantics>μ</semantics>g/mL. Pediocin did not show an inhibitory effect.